Productivity and Efficiency of Plywood Peeling: A Case Study - Effendi , Rachman (1990)
In the wood based industries, the veneer and plywood manufacturing is the second largest contributor to the Malaysian economy. The process of the improvement of plywood peeling involves increasing the productivity of mill and efficiency of resource use. Productivity implies the utilization of our resources efficiently and effectively. Thus, the objectives of this study is to determine the time consumptions, recovery rate, productivity and relationship between output and input of three types of lathe of an integrated plywood factory in Peninsular Malaysia. Productivity was defined as the ratio of output to input. Recovery was defined as the ratio of green veneer output to the volume of log input. Time consumption is the time consumed by individual processing elements and total cycle time. Three peelers (9 feet lathe, 5 feet lathe and 5 feet aristo lathe) were studied during the 14 days of peeling activities from 19 May to 4 June 1990. Data were collected from the three types of peelers and on four input factors (log, input, capital, utilities and labour cost). The study measure the time spent in the peeling process of peelers and total input value consumed by the peelers. Time data were collected on the peeling process namely charging, loading to the lathe, rounding-up, peeling, reeling, removing core, cleaning the knife and delay. Volume, value of veneer and four input factors were also recorded throughout this study. The regression analysis was used to determine relationship between output and input as factor production of veneer. The results showed that productivity per hour of 9 feet lathe, 5 feet lathe and 5 feet aristo lathe were 6.87 m , 3.99 m3 and 4.20 m3 respectively. Time required to produce one m3 of green veneer by using 9 feet lathe, 5 feet lathe and 5 feet aristo lathe were 8.74 minutes, 15.04 minutes and 14.28 minutes respectively with the recovery rate of 69.10%, 67.07% and 79.77% respectively. Total productivity of 9 feet, 5 feet and aristo lathe per M$ 1,000 were 2.62 m3, 2.55 m3 and 3.58 m3 respectively and total productivity in ratio of output value per all inputs value were 1.2013, 1.1664 and 1.6414 respectively. The increasing costs of labour and utilities are not influenced by the production of veneer. The green veneer production increases 0.8 percent with the increase 1 percent of log input to the peeler. The increase of 1 percent of capital, the green veneer production will increase 0.07 percent. Log input variable has the greatest influence to the production of green veneer.